Medical planning for toxic releases into the community: the example of chlorine gas. Issue 4 (April 1989) - Baxter, P J; Davies, P C; Murray, V
Abstract : Emergency planning for a major accidental release of chlorine gas from industrial installations into the community is outlined for emergency services and hospitals. Realistic planning has been made possible with the advent of computer models for gas dispersion which may be used to estimate the numbers of deaths and casualties, according to their severity. For most purposes sufficient accuracy may be obtained by using a small number of computer analyses for the most serious reasonably foreseeable events under typical day and night weather conditions, and allowing for the emergency response to be scaled up or down according to the size of an actual release. In highly populated areas triage should be preplanned to deal with a large number of victims; field stations will be needed for the treatment and observation of minor casualties. The management and treatment of casualties is summarised. The best protection against a gas cloud is afforded by buildings whose windows, doors, and ventilation systems have been closed. Hospitals in the vicinity of an installation should draw up plans to protect patients and staff. Coordination in a disaster will require toxicological and epidemiological expertise and hospital plans should allow for this.